Pendampingan Pembuatan Sistem Informasi Wisata Berbasis Website Menggunakan Wordpress Desa Sajang Kecamatan Sembalun - Wasil, Muhammad; Sudianto, Aris; Sadali, Muhamad; Permana, Baiq Andriska Candra; Mahpuz, Mahpuz; Suhartini, Suhartini; Ahmadi, Hamzan; Gunawan, Indra; Fathurrahman, Imam; Kertawijaya, Lalu; Harianto, Harianto (Universitas Hamzanwadi, 2023)
Currently, technological developments have developed very rapidly and quickly, bringing about very big changes because they make the information obtained available quickly, easily, accurately and not limited by place and time. One example of developments in the world of technology is internet technology. With the existence of internet technology, the dissemination of information becomes more practical and easy to access anywhere, anytime, and anyone can access the information. Internet technology not only has an effect on business or trade development, but also has a role in the tourism sector. Because with internet technology, the delivery of information on tourist attractions can be more connected or interactive and the information is easy to obtain. East Lombok Regency, in Sembalun sub-district, especially in Sajang village, there are potential tourist destinations such as Mount Rinjani, Camping Grounds, and Waterfalls as well as Agrotourism, namely Coffee Gardens. This service activity helps design a web-based information system using WordPress which can introduce tourism potential to the community and tourists who want to know about tourist attractions in Sajang village. Keywords: System, Information, Sajang village, Web